Pengaruh Motivasi Kerja Islam dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Disiplin Kerja sebagai Variabel Intervening pada UD Indo Karya Stone Tulungagung - Singgi Baharudin Moor; Agus Eko Sujianto (ITB AAS INDONESIA Surakarta, 2022)
In this article, the focus of the research is the employees of Indo Karya Stone Tulungagung, who expects all employees to be able to work optimally to achieve the desired results. As for the purpose; 1) determine the effect of Islamic work motivation on employee performance; 2) determine the effect of the work environment on employee performance; 3) the influence of Islamic work motivation on employee performance through work discipline as an intervening variable; 4) the influence of the work environment on employee performance through work discipline as an intervening variable UD. Indo Karya Stone Tulungagung. This study uses a quantitative approach. The population in this study were UD Indo Karya Stone Tulungagung, with a sample of 30 people. The sampling technique used is purposive sampling. Data collection techniques using online questionnaires via google form. The analysis tool uses SPSS 25.00. The results of the study show that: (1) Islamic work motivation has a significant direct effect on employee performance; (2) the work environment directly does not have a significant effect on employee performance; (3) Islamic work motivation indirectly has a significant effect on employee performance through work discipline (4) the work environment does not indirectly have a significant effect on employee performance through UD work discipline. Indo Karya Stone Tulungagung. The limitation of this research is that it only examines the effect of work motivation, work environment, and work discipline, while other variables that affect employee performance are expected to be investigated by further researchers.